Effect of Plant Spacing and Harvesting Stage on Morphological Characteristics and Yield of Desho Grass (Pennisetum Glaucifolium L) at Adola sub-site of Bore Agricultural Research Center, Oromia Region, Ethiopia - Teshale Beyene (PT FORMOSA CENDEKIA GLOBAL, 2024)
In order to evaluate the effects of a combination of harvesting stage and plant spacing on the morphological features and yield of Desho grass, a study was carried out in the midland of the Guji zone. Three replications of a randomized full block design with 3*3 factorial arrangements were employed. Three plant spacings (10, 30, and 50 cm) and three harvesting stages (75, 105, and 135 days) are used in this experiment. All plots received an application of nitrogen, phosphate, and sulfur (NPS) fertilizer at a rate of 100 kg/ha-1 before to planting. Plot cover (PC), vigorousity, dry matter yield (DMY), plant height (PH), leaf length per plant (LLPP), number of leaves per plant (NLPP), number of tillers per plant (NTPP), leaf to steam ratio (LSR), and survival rate (SR) are among the statistics gathered. Every piece of data were exposed to SAS, 2002, version 9.0, GLM ANOVA methods. The findings showed that, with the exception of leaf to steam ratio and plot cover, all morphological features were significantly (p<0.01) impacted by the treatments. Ten*75 treatments yielded the lowest mean number of tillers per plant (NTPP) of 21.53, while fifty*135 treatments produced the highest number of tillers per plant (NTPP) of 59.3. 30*105 treatments produced the highest plant height (100.43 cm), while 30*75 treatments produced the lowest plant height